How Much Would China Gain from Power Sector Reforms? An Analysis Using TIMES and CGE Models - Timilsina, Govinda; Pang, Jun; Yang, Xi (World Bank, Washington, DC, 2019)
Many countries have undertaken market-oriented reforms of the power sector over the past four decades. However, the literature has not investigated whether the reforms have contributed to economic development. This study aims to assess the potential macroeconomic impacts of an element of the power sector reform process that China started in 2015. It uses an energy sector TIMES model and a computable general equilibrium model. The study finds that the price of electricity in China would be around 20 percent lower than the country is likely to experience in 2020, if the country follows the market principle to operate the power system. The reduction in the price of electricity would spill over throughout the economy, resulting in an increase in gross domestic product of more than 1 percent in 2020. It would also increase household income, economic welfare, and international trade.